Biathlon Sports Complexes Forming Peculiarities and their Creation Practice Review - Borodai, Artem; Borodai, Dmytro; Vysochin, Ivan; Rudenko, Taras (International Journal of Engineering and Technology, 2018)
Related to the growing popularity of winter sports in general including biathlon as one of the most spectacular among them, there is a need to study, in particular, biathlon sports complexes formation basic features and peculiarities. It is an extremely up-to-date issue in Ukraine, as biathlon is developing really quickly though infrastructure level of biathlon complexes and sports camps is far from perfection. Legal and theoretical foundation for the ski and biathlon structures design and construction is also incomplete. That is why one of the top priority tasks for detailed examination of modernization ways for already existing and new sports complexes creating is design experience analysis of already existing biathlon facilities in Ukraine and abroad.Ski and biathlon facilities developmental evolution has been analyzed in the article alongside with the determination of facility functional organization abroad, in CIS countries and Ukraine. Also determination of different biathlon facility types, mainly, biathlon center, biathlon complex, ski lodge and ski station has been done for more precise understanding of the object under consideration. Biathlon facilities in Germany, Finland, Slovenia, Italy, Russia, and Belarus have been studied. Domestic biathlon and ski-biathlon facilities have been analyzed as well. All these complexes have been examined according to same characteristic features, which resulted in their comparative analysis.Â Â